LOW BONE MINERAL DENSITY AMONG PATIENTS WITH NEWLY DIAGNOSED RHEUMATOID ARTHRITIS - Arain, Shafique Rehman; Riaz, Amir; Nazir, Lubna; Umer, Tahira Parveen (Journal of Ayub Medical College Abbottabad, 2016)
Background: Osteoporosis is an early and common feature in rheumatoid arthritis. Apart from other manifestations, Osteoporosis is an extra-articular manifestation of rheumatoid arthritis which may result in increased risk of fractures, morbidity, mortality, and associated healthcare costs. This study evaluates bone mineral density changes in patients with rheumatoid arthritis of recent-onset. Methods: This descriptive case series was conducted in the Rheumatology Department of a tertiary care hospital in Karachi. Data was prospectively collected from 76 patients presenting with seropositive or seronegative rheumatoid arthritis. Bone mineral density of these patients measured at lumbar spine and hip by using dual energy x-ray absorptiometry scan. Variables like age, gender, BMI, menstrual status, disease duration, erythrocyte sedimentation rate, vitamin D level, clinical disease activity index and seropositivity for rheumatoid arthritis were measured along with outcome variables. Results: A total of 104 patients fulfilling inclusion criteria were registered with 28 excluded from study. Among the remaining 76 patients, 68 (89.50%) were female, with mean age of patients (with low bone mineral density) as 50.95±7.87 years. Nineteen (25%) patients had low bone mineral density, 68.52% had low BMD at spine while 10.52% at hip and 21.05% at spine and hip both. Low bone mineral density was found higher in patients with seronegative 7 (50%) as compared to seropositive patients 12 (19.4%) (p-value 0.017), whereas low bone mineral density was found higher 12 (70.6%) among post-menopausal women. Conclusion: Low BMD was found in 25% of patients at earlier stage of the rheumatoid arthritis with seropositivity, age and menopausal status as significant risk factors.